Perancangan Sistem Informasi Pembelajaran Ekstrakulikuler Kepramukaan Pada SMK Fatahillah Cileungsi Berbasis Android - Guspriyatna Nurcahya; Harry Dhika; Iis Dewi Lestari (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2022)
This study aims to introduce scouting learning to students. The benefits of this research can increase students insight into scouting material with android application, so that learning is more efficient. Qualitative subjective research method with data colletion techniques observational documentation (observation), interview souces directly meet scout coaches and students. The research location is at SMK Fatahillah Cileungsi, Kp. Central, Cileungsi District, Bogor Regency. The result of this study increase insight into the material knowledge of scouting both to the author and user of the application later.